Remediation and recovery of Selenium (Se) from contaminated water environment - Wang, Zhongli (2023)
The current shortage of resources, such as water and raw materials, is a global and critical challenge. In addition, human industrial activities are worsening the shortage of available water resources through pollution and harming the sustainability of the ecological environment. These pollutants not only harm water resources, but also enter the food chain, affecting human health. Selenium (Se) is an environmental toxic contaminant that seriously threatens human health and water ecosystems. Meanwhile, it is also a scarce element that cannot be mined as a primary product but plays a crucial role in the industry.